Enhanced optical transmittance by reduced reflectance of curved polymer surfaces - Chen, Wenwen; Diao, Zhaolu; Dirks, Jan-Henning; Geiger, Fania; Spatz, Joachim P. (Macromolecular materials and engineering, 2017)
Subwavelength nanostructure arrays on surfaces improve their optical transmittance by reducing the reflection of light over a wide range of wavelengths and angles of incidence. A method to imprint a sub-100 nm nanostructure array on a large surface (Ø 20 mm) made from thermoplastic materials is reported. Transmittance through the flat polymer is improved by ≈6.5%, reaching values of up to 97.5%, after imprinting. The optical properties of the nanostructured samples are highly reproducible. After eight repeated imprinting operations with the same stamp, the transmittance of the nanostructured surface is decreased by less than 0.2%. Moreover, the nanostructures can also be imprinted on curved polymethylmethacrylate surfaces, achieving a maximum transmittance of 97%. This method to prepare large-scale antireflective nanostructures on flat and flexible curved polymer surfaces is of interest for the production of antireflective screens, optical devices, and biomedical devices such as contact lenses and intraocular lenses.